Clonal Spread and Genetic Mechanisms Underpinning Ciprofloxacin Resistance in Salmonella enteritidis - Zengfeng Zhang; Hang Zhao; Chunlei Shi (Foods)
Salmonella enteritidis is a major cause of foodborne illness worldwide, and the emergence of ciprofloxacin-resistant strains poses a significant threat to food safety and public health. This study aimed to investigate the prevalence, spread, and mechanisms of ciprofloxacin resistance in S. enteritidis isolates from food and patient samples in Shanghai, China. A total of 1625 S. enteritidis isolates were screened, and 34 (2.1%) exhibited resistance to ciprofloxacin. Pulsed-field gel electrophoresis (PFGE) results suggested that clonal spread might have persisted among these 34 isolates in the local area for several years. Multiple plasmid-mediated quinolone resistance (PMQR) genes, GyrA mutations in the quinolone resistance-determining region (QRDR), and overexpression of RND efflux pumps were identified as potential contributors to ciprofloxacin resistance. PMQR genes oqxAB, qnrA, qnrB, and aac(6’)-Ib-cr as well as GyrA mutations S83Y, S83R, D87Y, D87G, D87N, and S83Y-D87Y were identified. The co-transfer of the PMQR gene oqxAB with the ESBL gene blaCTX-M-14/55 on an IncHI2 plasmid with a size of ~245 kbp was observed through conjugation, highlighting the role of horizontal gene transfer in the dissemination of antibiotic resistance. Sequencing of the oqxAB-bearing plasmid p12519A revealed a 248,746 bp sequence with a typical IncHI2 backbone. A 53,104 bp multidrug resistance region (MRR) was identified, containing two key antibiotic resistance determinants: IS26-oqxR-oqxAB-IS26 and IS26-ΔISEcp1-blaCTX-M-14-IS903B. The findings of this study indicate that ciprofloxacin-resistant S. Enteritidis poses a significant threat to food safety and public health. The persistence of clonal spread and the horizontal transfer of resistance genes highlight the need for enhanced surveillance and control measures to prevent the further spread of antibiotic resistance.